Ligand-exchange processes on solvated lithium cations: Acetonitrile and hydrogen cyanide - Pasgreta, Ewa; Puchta, Ralph; Zahl, Achim; van Eldik, Rudi (European Journal of Inorganic Chemistry, 2007)
Solutions of LiClO in solvent mixtures of acetonitrile and water, or acetonitrile and nitromethane, were studied by Li NMR spectroscopy. Measured chemical shifts indicate that the Li cation is coordinated by four acetonitrile molecules. In the binary water/acetonitrile mixture, water coordinates more strongly to Li than acetonitrile such that addition of writer immediately leads to the formation of [Li(H O)]. The solvent-exchange mechanism for [Li(L)] (L = CHCN and HCN) was studied by using DFT calculations (RB3LYP/6-311+G* *). This process was found to follow a limiting associative mechanism involving the formation of relatively stable five-coordinate intermediates. The suggested mechanisms are discussed with reference to available experimental and theoretical data. © Wiley-VCH Verlag GmbH & Co. KGaA, 2007.